Serum IL-1?, IL-6, IL-8, and TNF-? levels in early diagnosis and management of neonatal sepsis - Kurt, A. Nese Citak; Aygun, A. Denizmen; Godekmerdan, Ahmet; Kurt, Abdullah; Dogan, Yasar; Yilmaz, Erdal (Hindawi Ltd, 2007)
Aim. To determine serum IL-1 beta, IL-6, IL-8, and TNF-alpha levels in neonatal sepsis at the time of diagnosis and after therapy, and to show the meaningful on the follow up. Methods. This prospective study was performed on newborns who were hospitalized for neonatal sepsis and who were classified as culture-proven sepsis (n = 12), as culture-negative sepsis ( n = 21), and as healthy newborns ( n = 17). Results. At the time of diagnosis, serum IL- 1 beta, IL-6, IL-8, and TNF-alpha levels of culture-proven sepsis were significantly higher than those of the control groups (P <.05). At the time of diagnosis, IL-1 beta, IL-6, IL-8, and TNF-alpha levels of culture-proven sepsis and culture-negative sepsis were significantly higher than levels at the seventh day after antibiotic treatment. Conclusion. Serum IL-1 beta, IL-6, IL-8, and TNF-alpha are mediators of inflammation and can be used at the diagnosis and at the evaluation of the therapeutic efficiency in neonatal sepsis. Copyright (c) 2007.
Keywords: Tumor-Necrosis-Factor; C-Reactive Protein; Colony-Stimulating Factor; Plasma-Levels; Bacterial-Infection; Antibiotic-Therapy; Cord-Blood; Interleukin-6; Neutrophil; Expression